Near-infrared photodetector achieved by chemically-exfoliated multilayered MoS2 flakes - Park, Min Ji; Park, Kisun; Ko, Hyungduk (ELSEVIER, 2018)
A near-infrared (NIR) photodetector built from chemically exfoliated multilayer MoS2 films was investigated. Devices that are photoresponsive to wavelengths up to 1550 nm were fabricated using 25-nm-thick MoS2 films. To the best of our knowledge, this is the first time such a detector was produced using chemical exfoliation. As the thickness was increased to 25 nm, the MoS2 flakes formed a nearly or fully continuous film with a 2H-dominant phase, and also exhibited enhanced NIR absorption up to 1550 nm. We conjecture that the defects formed during chemical exfoliation affect the intrinsic bandgap of MoS2, extending its spectral absorption range into the NIR range. Moreover, the responsivity of the device was enhanced by introducing plasmonic Ag nanocrystals. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: FEW-LAYER MOS2; HIGH-DETECTIVITY; TRANSITION; ULTRAFAST; DRIVEN